Creating, using, and sharing embodied information in the ultrarunning community on Instagram - Laura Williams; Andrew Cox; Andrea Jimenez (Information Research: An International Electronic Journal)
Introduction. This paper discusses how ultrarunners create, use, and share embodied information on Instagram. The research explores how embodied information is used beyond the run, asking how visual social media digital practices shape how information is created, used, and shared.